המנגן הדמוני: מדוע ניסה ההלך, לשווא, לזנוח את "הניגון" בכוכבים בחוץ? בחינה חוזרת - שהם ראובן (מכאן, 2017)
Since the publication of Stars Outside (Kohavim Bahuts, 1938), people have asked: Why did Alterman’s wayfarer attempt to abandon the tune? The prevailing responses declared that this wayfarer was experiencing an inner confrontation between his commitment to the tune and his commitment to the physical world and the fragile history of his time and place. This confrontation, scholars claim, ultimately leads to a decision: the wayfarer accepts his problematic goal of becoming a "roving" poet, as reflected in poems such as "The Strange Poem"(Ha’shir Hazar), "A Letter" (Igeret) and "Themselves Alone" (Hem Levadam). In this article Shoham seeks to claim, contrary to prevailing opinion, that there is an irreconcilable conflict between these objectives that persisted throughout Alterman’s creative life, as depicted in Inn of the Spirits (Pundak Haruhot), Dove City (Ir Hayona) and Summer Revelry (Hagigat Kayits). In Stars Outside, this struggle is the eternal conflict in which the speaker, Homo Poeticus, repeatedly sacrifices his doppelgänger, Homo Naturalis.